Pengembangan Media Pembelajaran Audio Visual pada Keterampilan Menulis Puisi Melalui Strategi Pembelajaran Think Talk Write (TTW) bagi Siswa Kelas X - Br Purba, Yosa Agrevina; Rita, Rita; Kartika, Rika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2025)
This study aims to develop and evaluate audio-visual learning media for enhancing poetry writing skills using the Think-Talk-Write (TTW) strategy for grade X students. The research follows the Research and Development (R&D) method, utilizing the 4D model (Define, Design, Develop, Disseminate) developed by Thiagarajan. Data were collected through questionnaires using a Likert scale for quantitative analysis, while qualitative data were obtained from expert evaluations, comments, and suggestions. The study involved four validators—two material experts and two media/design experts—to assess the feasibility of the developed media. The research was limited to the development stage, where material validators assigned an average validity score of 76%, categorized as "very feasible", while media/design validators provided an overall score of 72%, classified as "feasible". These findings confirm that the audio-visual learning media for poetry writing skills is valid, practical, and effective for use in school learning environments, making it a potential tool to enhance student engagement and creativity in poetry writing. Future research should explore the implementation stage and assess its impact on students' learning outcomes.